Upper‐Atmosphere Mass Density Variations From CASSIOPE Precise Orbits - Andrés Calabia; Shuanggen Jin (Space Weather)
Abstract Thermospheric mass density (TMD) measurements are invaluable to accurately estimate and predict the position and velocity of orbiting objects in Low Earth Orbit (LEO). Existing observational methods and predictive models have some problems (e.g., accuracy, resolution, coverage, cost, etc.) to describe and forecast the actual air drag variations as required for practical applications. With the increasing number of LEO satellites equipped with high‐precision Global Navigation Satellite System (GNSS) receivers, the precise orbits can be used to obtain non‐gravitational accelerations, and therefore estimate TMD variations. In this study, TMD is estimated from the precise orbits of CAScade SmallSat and IOnospheric Polar Explorer (CASSIOPE) at one‐second time step, and the TMD variations following the February 2014 geomagnetic storm are investigated. Using this method, a more detailed description than previous methods and empirical models is given with short‐term TMD variations during geomagnetic storm conditions. The empirical model NRLMSISE‐00 shows less pronounced and more averaged variations, while CASSIOPE‐derived TMD can reflect the abrupt disturbances triggered by the geomagnetic storm. CASSIOPE TMD shows a correlation of 72.4% to the merging electric field Em index, while the NRLMSISE‐00 model shows a correlation of 42.1%.